OPTIMALISASI KREATIVITAS PESERTA DIDIK DALAM PEMBELAJARAN KECAKAPAN HIDUP - Aziz, Safrudin (STAIN Pamekasan, 2010)
Abstract: Creativity is the process of using the imagination and expertise to bear new ideas, unique and useful. Creativity can be developed through the 4 P (person, process, press and product). In the process of learning, creativity of learners can be developed through life skills education. The learning process based on developing creativity of students in life skills education can be pursued through the following activities: Firstly, introduction, including a brief description of the content skills that will be studied, explaining the relevance of the content of new skills with everyday life, as well as describing of competence that learners should be achieved. Secondly, the presentation (including: exploration, elaboration, confirmation). Thirdly, the closing activities; teachers do formative evaluation and authentic assessment of learning activities, life skills have been implemented, providing feedback for the implemented activities, and designing follow up activities in the form of remedial learning, enrichment, and providing structured or unstructure tasks for the learners.